Co-ingestion of Antioxidant Drinks With an Unhealthy Challenge Meal Fails to Prevent Post-prandial Endothelial Dysfunction: An Open-Label, Crossover Study in Older Overweight Volunteers - Muggeridge, David J.; Goszcz, Katarzyna; Treweeke, Andrew; Adamson, Janet; Hickson, Kirsty; Crabtree, Daniel; Megson, Ian L. (Frontiers in Physiology, 2019)
Eating a high calorie meal is known to induce endothelial dysfunction and it is reported that consuming drinks rich in antioxidants may be protective against this. In this study we assessed the effects of three antioxidant drinks with considerable disparity in their antioxidant content on endothelial function. Seven healthy volunteers (BMI 25-35; mean age 57± 3 years; 1 male, 6 females) completed 4 trials in a randomised counterbalanced design. Water (control), orange juice, green tea or red wine were consumed with a high calorie meal (>900 kcal). Endothelial function was measured by flow-mediated dilatation immediately before (fasted, baseline) and 2 hours after the meal. Blood samples were also obtained for lipid and glucose analysis, plasma nitrite (NO2-) and oxidised low density lipoprotein (ox-LDL). Participants returned after a minimum 3 days washout to complete the remaining arms of the study. The results found that the high calorie meal induced a substantial increase in triglycerides, but not cholesterol or glucose, at 2 hours after meal ingestion. FMD was significantly reduced by ~35% at this timepoint, but the effect was not attenuated by co-ingestion of any of the antioxidant drinks. Reduced FMD was mirrored by a reduction in NO2-, but ox-LDL was not increased at 2 hours after the meal. None of the undertaken measures were influenced by the antioxidant drinks. We conclude that co-ingestion of none of our test antioxidant drinks protected against the substantial post-prandial endothelial dysfunction induced by an unhealthy meal challenge.